O montanhismo no Rio de Janeiro: eugenia, higienismo e a febre esportiva, c.1900-1920 - Tauan Nunes Maia (2019)
The aim of this study is to understand how mountaineering was inserted into the set of transformations that took place in the city of Rio de Janeiro during the first two decades of the twentieth century. Thus, research in available publications in newspapers was created in the portal of the Digital Library of the National Library. Such publications indicate that mountaineering was imbued with a new urban social life in a country that sought modernization and progress. However, in part, such changes occurred in order to maintain the already existing social hierarchy, by the precepts of eugenics and hygienism. Thus, sports, like mountaineering, began to gain spotlight for being considered tools for moral, physical, and intellectual education. Mountaineering was seen as a key element in the construction of a strong and virile society, which was able to change the bodies of the nation because it made use of elements such as competition, selection of the strongest, evolution, and heredity. During that period, the press associated with mountaineers the values expected of a modern man, such as courage, bravery, virility, glory, and strength. A strategy of spreading a new body model coupled with new standards of wellbeing and health resulted in a new body image construction. Mountaineering slowly became incorporated into the daily lives of the working class, making it one of the only activities they practiced. Regarding gender issues, mountaineering contributed to the creation of new images for women, who previously were expected to have a certain standard of beauty and civility, through practice of the sport and the physical values and attributes,. Mountaineering can also be seen as a fight and affirmation tool of women in that time-space. There was, at that time, a search for the institutionalization of mountaineering. Such practice was permeated by values, desires, and sensibilities associated with modernity, such as comparing results, overcoming limits, performing activities in extreme situations, valuing technological development, building national identities, emotional control, and exalting the concept of beauty. In the same way, it began to adopt codes of capitalist society, such as production, precision, dispute, and performance. The narratives associated with mountaineering brought to the city an image of brightness, modernity, and, in some cases, veiled criticisms. In relation to the concept of modern identity, mountaineering was directly related to the new social dynamics because it valued the idea of spectacle and consumption in peoples perceptions. Thus, the risk-adventure binomial becomes essential in the adoption of behaviors, since industrial capitalism exercised a disciplinary power. It should be noted that mountaineering can be understood as a mechanism of self-identification and social distinction, softening the ills of living in a backwards city and in a country undergoing profound changes. As social distinction was also associated with pleasure, happiness, familiarity, cooperation, and patriotism/nationalism, mountaineering was seen as the foundation of what was expected of a modern and peaceful nation. Thus, the values attributed to mountaineering, such as challenge, physical exercise, corporal aesthetics, honesty, and morality, understood as a school of virtues, were essential in a country that underwent profound transformations and sought the path to civilization.